(untitled) (The Journal of Modern Project Management, 2022)
This paper investigates the value of servitization in the context of real estate development projects. A qualitative case study research approach is adopted, and the principles of the Delphi study applied. The findings indicate that the outputs of the real estate development projects have become systems of both project components and added services. These systems are the result of servitization strategies in the real estate development projects that shift the industry focus from only designing and selling a physical output to delivering a system of services integrated to the project, which together are capable of adding more customer value. The research identifies several types of services, which are used to develop four categories of servitization in the real estate development projects. The research develops the value chain of servitization strategy and it was found that offering services in real estate development projects is an incremental process; offering basic services (order qualifier) adds additional value for customers and makes the project ‘more’ valuable. However, basic services will not ensure competitive success. More advanced services such as customer-orientated-services need to be provided to enhance the project’s competitive advantage (order-winners).However, it the system solutions that shape the order-winning criteria of the construction industry.